Phenol Content and Peroxidase Enzyme Activity in Soybean Infected with Xanthomonas axonopodis pv glycines with the Application of Bacillus subtilis JB12 and Bacillus velezensis ST32 (Baghdad Science Journal, 2023)
Xanthomonas axonopodis pv glycines (Xag) is a pathogen that causes pustule disease in soybeans. Many techniques for controlling this disease have been widely developed, one of which is the use of biological agents. Bacillus sp. from the soybean phyllosphere is a biological agent that has the potential to suppress the development of pustule disease. One of the biological control mechanisms is through biochemical induction of plant resistance which includes the accumulation of phenols, salicylic acid compounds, and peroxidase enzymes. Bacillus subtilis JB12 and Bacillus velezensis ST32 are two bacteria isolated from the soybean phyllosphere which have previously been known to suppress Xag through an antibiosis mechanism. This study aimed to determine the potential of Bacillus subtilis JB12 and Bacillus velezensis ST32 in inducing soybean resistance against Xag infection. This research was carried out in two stages, the induction of resistance tosoybean germination and an experiment in a greenhouse. This study consisted of 4 treatments and 5 replications, including P0 (Xag inoculation), P1 (Bacillus subtilis JB12 inoculation), P2 (Bacillus velezensisST32), and P3 (Bacillus subtilis JB12 + Bacillus velezensis ST32 inoculation). Observations were made on the content of phenolic compounds, peroxidase enzyme activity, and the development of soybean pustule disease. The results showed differences in phenol content and peroxidase activity at the two stages of the study.Seed treatment with both isolates of Bacillus sp was able to increase the phenol content of soybean sprouts up to 3 - 5 days after inoculation (dai). Phenol content then decreased and was followed by an increase in the peroxidase activity up to 7 dai. The application of Xag and two isolates of Bacillus sp. in soybean plants caused the phenol content to fluctuate and peroxidase activity to decrease. Bacillus subtilis JB12 in general played a better role in increasing phenol content and peroxidase enzyme activity in soybean than Bacillus velezensis ST32. The application of two isolates of Bacillus sp. was not able to prolong the incubation period and reduce the severity of the pustule disease 14 days after inoculation.